Humanistic and Educational Analysis of Biology Teacher Readiness in Implementing a Deep Learning Approach at State Senior High School 7 North Bengkulu - Eri Yanto; Asmi Astuti; Merri Sri Hartati (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study aims to provide a humanistic and educational analysis of Biology teacher readiness in implementing a deep learning approach at State Senior High School 7 North Bengkulu. The deep learning approach is positioned as a learning strategy oriented toward higher order thinking skills, deep conceptual understanding, student autonomy, and reflective learning as key elements of humanistic education. This research employed a qualitative descriptive method. Data were collected through in-depth interviews with Biology teachers, document analysis of lesson plans and learning materials, and questionnaires involving students as respondents. The findings indicate that Biology teacher readiness in implementing the deep learning approach is generally in the “ready” category. Teachers have understood the importance of student-centered learning and the urgency of developing critical and reflective thinking; however, they still face challenges in systematically designing deep learning activities, integrating supportive learning media, and consistently aligning assessment with deep learning principles. These results highlight the need for schools and related stakeholders to provide continuous professional development, intensive training, and mentoring so that the deep learning approach can be implemented more effectively and sustainably in Biology learning as part of a broader humanistic education agenda.